Seed Development and Maturation in Ashwagandha (Withania somnifera Dunal.) - V VAKESWARAN; MB ARUNKUMAR; V KRISHNASAMY (Seed Research, 2026)
Studies were undertaken at the Department of Seed Science and Technology, Tamil Nadu Agricultural University, on Ashwagandha (Withania somnifera Dunal) var. Jawahar Asgand 20, to trace the pattern of seed development and maturation. The seeds attained physiological maturity at 35 DAA when seed dry weight was at maximum and it was also associated with the colour change of the fruit from orange to deep red. The developing seeds attained the germination potential of 21 per cent at 21 DAA and reached the maximum of 63.5 per cent at 42 DAA. The root and shoot length of seedlings, dry matter content and vigour index values increased gradually as the seed reached maturation. Electrical conductivity of seed leachate, enzyme activities such as o-amylase, catalase and peroxidase decreased gradually during seed development and maturation. Harvest maturity of seed was reached at 42 DAA when seed germination and vigour were at peak. High moisture content of fruits and seeds at initial stages got reduced to 60.6 and 32.3 per cent respectively at 42 DAA.